Lucean Arthur Headen : the making of a black inventor and entrepreneur - Snider, Jill D. (University of North Carolina Press, 2020)
"Born in Carthage, North Carolina, Lucean Arthur Headen (1879-1957) grew up amid former slave artisans. Inspired by his grandfather, a wheelwright, and great-uncle, a toolmaker, he dreamed as a child of becoming an inventor. His ambitions suffered the menace of Jim Crow and the reality of a new inventive landscape in which investment was shifting from lone inventors to the new 'industrial scientists.' But determined and ambitious, Headen left the South, and after toiling for a decade as a Pullman porter, risked everything to pursue his dream. He eventually earned eleven patents, most for innovative engine designs and anti-icing methods for aircraft. An equally capable entrepreneur and sportsman, Headen learned to fly in 1911, manufactured his own 'Pace Setter' and 'Headen Special' cars in the early 1920s, and founded the first national black auto racing association in 1924, all establishing him as an important authority on transportation technologies among African Americans. Emigrating to England in 1931, Headen also proved a successful manufacturer, operating engineering firms in Surrey that distributed his motor and other products worldwide for twenty-five years. Though Headen left few personal records, Jill D. Snider recreates the life of this extraordinary man through historical detective work in newspapers, business and trade publications, genealogical databases, and scholarly works"--